The effect and mechanisms of melatonin on the proliferation and apoptosis of lung cancer cells. Issue 2 (1st February 2022) - Liu, Hui; Wang, Fang; Zhao, Jun; Zhang, Xiaoling; Zeng, Zhen; Wang, Shasha; Guan, Jingzhi; Qin, Haifeng
ABSTRACT: The aim of the present study was to observe the effects and mechianisms of melatonin on the proliferation and apoptosis of lung cancer (LC) cells. A549 cells were treated with a concentration gradient (0–100 μM) of melatonin for 24 hours, and cell viability was detected by XTT ((2, 3-Bis-(2-methoxy-4-nitro-5-sulfophenyl) −2H-tetrazolium-5-carboxanilide)) colorimetry. Melatonin with a concentration of 50 μM was selected to interact with the LC cells for ten days, and then a colony formation assay was used to detect the proliferation of the LC cells. TUNEL (Terminal-deoxynucleoitidyl Transferase Mediated Nick End Labeling) staining was used to evaluate the amount of apoptosis in the two groups. Finally, Western blotting was used to detect the expression levels of related proteins in the p38MAP (mitogen-activated protein) signaling pathway. Meanwhile, another experiment, CCK-8 cell proliferation test, was conducted to detect the OD540 absorbance of LC cells at 24, 48, 72, and 96 hours. Melatonin inhibited the proliferation of LC cells in a concentration-dependent (5–100 μM) manner (P < 0.05), and inhibited the proliferation of LC cells in a time-dependent (0–96 hour) manner (P < 0.05). Melatonin (50 μM) could significantly inhibit the colony formation ability of LC cells (P < 0.05). The ratio of LC cells in the G0/G1 phase in the melatonin group increased, while the ratio of cells in the G2/M and S phase was significantly reduced (P < 0.05). Melatonin significantly promoted the apoptosis of LC cells (P < 0.05) and activate the phosphorylation of p38 (P < 0.05).